Enhancing Speaking Skills through Performance Assessment: A Study in Junior High School - Wulan Fadila; Edi Trisno (STAI Hubbulwathan Duri, 2025)
The implementation of performance assessment, particularly in speaking skills, presents significant challenges for teachers. Many still rely heavily on traditional paper-based tests, which may not effectively measure students' oral proficiency. This study aims to explore the types of speaking assessments used by junior high school teachers and to identify the challenges they face in applying performance-based assessments. This research employed a descriptive qualitative design, focusing on four junior high school English teachers as informants. Data were collected through classroom observations and in-depth interviews, then analyzed thematically to uncover assessment practices and implementation barriers. Findings revealed that teachers primarily used three types of speaking assessments: intensive, responsive, and interactive. However, the implementation process presented several challenges. One major issue was related to the purpose of assessment, as teachers often struggled to clearly identify and align assessment tasks with specific learning objectives. Fairness also emerged as a concern, particularly in managing the wide range of student speaking abilities and ensuring that all students were evaluated equitably. Additionally, grading posed difficulties, with teachers expressing uncertainty in applying consistent and objective assessment criteria, which led to subjective and sometimes inconsistent scoring. These findings suggest a gap between the intended use of performance assessment and its practical execution. The lack of clear guidelines and assessment training contributes to inconsistencies and challenges in evaluating students’ speaking skills effectively. Performance assessment in speaking remains underutilized due to practical barriers. Professional development focusing on assessment literacy and standardized grading rubrics is recommended to support teachers in implementing fair and effective speaking assessments.